Program Magang Asisten Guru terhadap Kesiapan Mahasiswa Menjadi Guru di FKIP Matematika Universitas Muhammadiyah Surakarta - Lestiani, Rista Novia, Prof. Sutama, M.Pd (2017)
Research have four purpose. (1) to examine contribution of the implementation of learning abilities, ICT as a medium of learning and social abilities against the readiness of students (2) to examine contribution to the implementation of learning abilities against the readiness of students (3) to examine contribution usage of ICT as a medium of learning against the readiness of students (4) to examine contribution of social capability against the readiness of students. This research is a research kuantitatif by design korelasional. The population of this research is the entire student mathematics education force 2013 Muhammadiyah University of Surakarta who have been following the Internship Program Assistant teacher. Sampling techniques using simple random sampling, with the number of samples as much as 143 students. Now using the method of data collection and documentation. Technique of data analysis using multiple regression analysis. This research with α = 5%, obtained the conclusion that: (1) there is a contribution implementation of learning abilities, usage ICT as a medium of learning and social abilities against the readiness of students, with contributions amounting to 47% (2) there is a contribution towards student readiness implementation of learning, with the contribution of 32.97% (3) there is the contribution usage of ICT as a medium of learning ability of student readiness, with contributions in the amount of 11.74% (4) there is a contribution towards social ability of student readiness, with the contribution of 2.30%.